2009
DOI: 10.1002/cncr.24485
|View full text |Cite
|
Sign up to set email alerts
|

Pathway sensitivity analysis for detecting pro‐proliferation activities of oncogenes and tumor suppressors of epidermal growth factor receptor‐extracellular signal‐regulated protein kinase pathway at altered protein levels

Abstract: BACKGROUND: Mathematic models and sensitivity analyses of biologic pathways have been used for exploring the dynamics and for detecting the key components of signaling pathways. METHODS: The authors previously developed a mathematic model of the epidermal growth factor receptor‐extracellular signal‐regulated protein kinase (EGFR‐ERK) pathway using ordinary differential equations from existing EGFR‐ERK pathway models. By using prolonged ERK activation as an indicator that may lead to cell proliferation under ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…24 A common method of modeling biological pathways is to formulate coupled ordinary differential equations (ODEs). [25][26][27][28][29][30][31][32][33][34][35][36] However, to formulate and solve ODE models, both the network structure and parameter estimates are required. Yeast two-hybrid (Y2H), [37][38][39][40] fluorescence resonance energy transfer (FRET) 41 or chromatin immunoprecipitation (ChIP)-DNA microarray techniques [42][43][44][45] have all been used to identify network interactions.…”
Section: Insight Innovation Integrationmentioning
confidence: 99%
“…24 A common method of modeling biological pathways is to formulate coupled ordinary differential equations (ODEs). [25][26][27][28][29][30][31][32][33][34][35][36] However, to formulate and solve ODE models, both the network structure and parameter estimates are required. Yeast two-hybrid (Y2H), [37][38][39][40] fluorescence resonance energy transfer (FRET) 41 or chromatin immunoprecipitation (ChIP)-DNA microarray techniques [42][43][44][45] have all been used to identify network interactions.…”
Section: Insight Innovation Integrationmentioning
confidence: 99%
“…Our mathematical model, was derived from the conventional models313233343538 and drug-target binding kinetics34 with the parameters fitted to the median IC50 values of potent inhibitors. Variation of the IC50 from 5 nM to 50 nM led to comparable degree of variations in the predicted GI50 values (9–95 nM, 19–195 nM and 10–99 nM for EGFR, BRaf and MEK inhibitor respectively).…”
Section: Resultsmentioning
confidence: 99%
“…These also provide useful knowledge for developing drug or drug combination targeted mathematical models for a number of pathways targeted by drugs and drug combinations (e.g. EGFR-ERK3132333435, apoptosis3637, NFκB1617, Wnt19 and disease-relevant metabolic22232425 pathways).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dynamical modeling helped uncover the importance of phosphorylation events and effects due to gain or loss of protein-protein interactions in establishing novel pathway crosstalk. Using mass action law, our previous studies showed that dynamical modeling is a powerful approach to identify the “Achilles heel” of a cancer network, or genes sensitive to perturbations that may alter disease outcome [ 186 ]. Dynamical modeling may be applied to neuroblastomas, once key regulatory modules have been discerned via network-based modeling.…”
Section: Modeling Neuroblastoma-derived Big Datamentioning
confidence: 99%